Prevalence of Anxiety, Depression, and Post-Traumatic Stress Disorder among Children and Adolescents with Cancer: A Systematic Review and Meta-Analysis. (March 2022) - Al-Saadi, Laila S.; Chan, Moon Fai; Al-Azri, Mohammed
Assessment of psychological and emotional disorders is an important indicator of well-being among children and adolescents with cancer. This review aimed to determine the prevalence rates of three major psychological disorders in this population, including anxiety, depression, and post-traumatic stress disorder (PTSD). Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Various databases were searched to identify cross-sectional studies assessing anxiety, depression, and PTSD among children and adolescents with cancer. The Joanna Briggs Institute checklist was used to assess research quality. Of the 40 studies included in the literature review, 33 measured anxiety, 28 focused on depression, and nine assessed PTSD. A total of 18 studies were incorporated into the meta-analysis, with pooled prevalence rates of anxiety, depression and PTSD found to be 13.92% (n = 1, 971; 95% confidence interval [CI] = 10.23–18.07%), 20.43% (n = 1, 990, 95% CI = 13.85–27.93%), and 20.90% (n = 755, 95% CI = 13.28–29.73%), respectively. Mental health and psychological interventions are essential for children and adolescents diagnosed with cancer. Future work should be undertaken in different regions, such as the Middle East or Africa, or South America when assessing the prevalence of psychological disorders in children and adolescents diagnosed with cancer.